Model-based extension of high-throughput to high-content data - Pfeifer, Andrea; Kaschek, Daniel; Bachmann, Julie; Klingmüller, Ursula; Timmer, Jens (BMC systems biology, 2010)
High-quality quantitative data is a major limitation in systems biology. The experimental data used in systems biology can be assigned to one of the following categories: assays yielding average data of a cell population, high-content single cell measurements and high-throughput techniques generating single cell data for large cell populations. For modeling purposes, a combination of data from different categories is highly desirable in order to increase the number of observable species and processes and thereby maximize the identifiability of parameters.
Gesehen am 02.05.2023